Lyddie - Paterson, Katherine (New York Puffin Books, 1992)
Impoverished Vermont farm girl Lyddie Worthen is determined to gain her independence by becoming a factory worker in Lowell, Massachusetts, in the 1840s.
Keywords: Self-reliance -- Fiction; Work -- Fiction; Factories -- Fiction; Textile workers -- Fiction; Lowell (Mass.) -- Fiction